2022 Roger A. Mann Award Winner: Total Ankle Replacement vs Arthrodesis (TARVA) Randomized Controlled Trial: 2 Year Results. Issue 4 (November 2022) - Goldberg, Andrew J.; Chowdhury, Kashfia; Molloy, Andrew P.; Davies, Mark Bowen; Hepple, Steve; Thomas, Rhys H.; Siddique, Malik S.; Loveday, David T.; Dhar, Sunil; Bing, Andrew J.; Clough, Timothy; Bendall, Stephen P.; et al.
Category: Ankle Arthritis; Ankle; Hindfoot; Other Introduction/Purpose: End-stage ankle osteoarthritis (EOA) causes severe pain and chronic disability. Once non operative measures have been exhausted the two main surgical treatments include total ankle replacement (TAR) and ankle fusion (AF). Systematic reviews have confirmed that both procedures are effective but there has never been a robust randomised multicentre level I study comparing the two treatments. Our objective was to investigate and compare the clinical and cost effectiveness of TAR against AF in the treatment of end-stage ankle osteoarthritis in patients aged 50-85 years. Methods: TARVA is a multi-centre, parallel-group, open label randomised trial. Patients with EOA, aged 50-85, suitable for either procedure were recruited at 17 UK hospitals. Randomisation was carried out using a secure on-line service and was stratified by surgeon and the presence or absence of adjacent joint OA (based on an independently reviewed preoperative MRI scan). Participants were randomised 1:1 to either TAR or ankle arthrodesis. The primary outcome was the change in the Manchester Oxford Foot & Ankle Questionnaire (MOXFQ) walking/standing domain scores between pre-operation and 52 weeks post- operation. Secondary outcomes measures included FAAM; FAAM (ADL); and Sport subscale scores. Quality of life was measured using the EQ-5D-5L. Total range of tibia to floor motion was measured using a validated method. Health economic analysis used mean incremental cost per quality-adjusted life years (QALY) gained. Analysis was by intention to treat. The trial registration is ISRCTN60672307. Results: Of 933 eligible patients 303 were randomised. 282 underwent surgery. Mean age 68 (71% male). Aetiology was post- trauma in 55.3%, and inflammatory in 7.1%. Groups were well balanced at baseline on all parameters. 54% TARs were fixed bearing. 61% of fusions were performed arthroscopically. At 2 years the adjusted mean difference in the change in MOXFQ W/S between TAR & AF was -4.4(95% CI -11.38 to 2.68, p=0∙23). Post hoc analysis of the commonest implant type (fixed bearing TAR) did show a statistically significant improvement over AF (p=0∙04, -8.9, 95% CI -17.2 to -0.6). Secondary outcomes, EQ5D-VAS and FAAM were significant. Complications included wound healing issues (13.8% vs 5.5%); nerve injuries (4.3% vs 0.7%). 11.8% of AF patients had plain radiographic evidence of non-union but only 6.9% had symptoms. Reoperation rate was 7.2% for TAR vs 5.2% for AF; and revision rate was 0.7% for TAR vs 2.8% for AF. Conclusion: Patients improved in all outcomes in both arms. We did not show a significant difference in our primary outcome measure between TAR and AF overall(p=0.23), but did show significance when fixed bearing TAR alone was compared against AF(p=0.04). Secondary outcomes did show significance. Adjacent joint arthritis increases the size of effect noted between arms. There were more wound healing issues and nerve injuries in TAR group. The symptomatic non-union rate for AF is 6.9%. TAR is likely to be cost-effective compared to AF at the NICE cost-effectiveness threshold of £20, 000 per Quality Adjusted Life Year gained over the patients' lifetime.